Dividend Signaling Hypothesis: Evidence from the Spanish Market - Colmenares Matute, Paula (2016)
The purpose of this study is to examine whether or not the dividend signaling theory holds in the Spanish market. Concretely, it aims to investigate whether the dividend changes that Spanish public firms make convey any information about the future earnings of the company. To that end, the relation between dividend increases and decreases with future earnings changes is analysed separately. The impact of dividend changes on future earnings should be positive as proposed by the dividend signaling hypothesis. A linear model is used to study this relation over a sample of 158 Spanish public companies during a ten years period of time, from January 2004 to December 2013. The results reveal that in the case of Spain, the company’s dividend changes do affect future earnings changes. However, the results are not very conclusive. The findings support a positive relationship between dividend decreases and future earnings in changes. Nonetheless, a negative relation is found for the dividend increases despite it is not very significant. This last finding is the contrary to the expectation. Furthermore, the future earnings reaction to the dividend changes is examined year by year. It can be concluded that there is a change since 2008. I conjecture that this is due to the economic and financial crisis that Spain was experiencing. However, those results are not very reliable as most of them are not empirically significant. Therefore, there is a need to conduct further studies in this field.